Performance measurement of organic tea supply chain with supply chain operation references (Case study of active tegal subur farmer group, Kulon Progo) - Soejanto, Irwan; Pratama, Ferdiansyah Aji; Nursubiyantoro, Eko (OPSI, 2024)
Tegal Subur Aktif Farmer Group is one of the organic tea producers located in Menoreh Hills, precisely in Nglinggo, Pagerharjo, Samigaluh, Kulon Progo. The efforts carried out by this farmer group include the procurement of tea ingredients, the provision of production facilities, the cultivation and maintenance of tea plants, the processing of agricultural products and trade in general. Processed organic tea products, such as green, black, yellow, and roasted, are produced.   Farmer groups have uncertain orders that can only be fulfilled partially, which can still affect customer satisfaction. In total, there are 95.39% of uncertain orders that can be fulfilled in the period August 2021 – March 2022. This is related to production planning with actual production caused by uncertain or regular supply of raw materials. If the collection of raw material supply is still carried out, it causes cost losses in collecting raw materials. The Tegal Subur Aktif Farmer Group has never measured its supply chain performance. If measurement is not carried out, supply chain performance may develop slowly. This study aims to measure the organic tea supply chain's performance and determine which indicators need improvement. This research uses the Supply Chain Operation References (SCOR) and Analysis Hierarchy Process (AHP) methods. Based on the data processing carried out, by measuring supply chain performance with Supply Chain Operation References (SCOR) and Analysis Hierarchy Process (AHP), the supply chain performance of the Active Tegal Subur Farmer Group can be improved.